2004
DOI: 10.1016/s0002-9440(10)63173-2
|View full text |Cite
|
Sign up to set email alerts
|

C5a-Induced Gene Expression in Human Umbilical Vein Endothelial Cells

Abstract: The endothelium plays a critical role in the inflammatory process. The complement activation product, C5a, is known to have proinflammatory effects on the endothelium, but the molecular mechanisms remain unclear. We have used cDNA microarray analysis to assess gene expression in human umbilical vein endothelial cells (HUVECs) that were stimulated with human C5a in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 51 publications
1
109
2
2
Order By: Relevance
“…3A). DNFB also induced secretion of C5a, well known stimulator of anaphylaxis (21). In vivo down-regulation of HDAC3 exerted a negative effect on secretion of MCP1, C5a, TIMP1, and sICAM1 in BALB/c mice stimulated with DNFB (Fig.…”
Section: Hdac(s) Inhibited An Interaction Between Hdac3 Andmentioning
confidence: 79%
“…3A). DNFB also induced secretion of C5a, well known stimulator of anaphylaxis (21). In vivo down-regulation of HDAC3 exerted a negative effect on secretion of MCP1, C5a, TIMP1, and sICAM1 in BALB/c mice stimulated with DNFB (Fig.…”
Section: Hdac(s) Inhibited An Interaction Between Hdac3 Andmentioning
confidence: 79%
“…C5a-stimulated human umbilical vein endothelial cells exhibit an increased expression of genes involved in endothelial adhesion, migration, and angiogenesis. 32 In addition, it has recently been shown that C3a and C5a contribute to the angiogenesis associated with age-related macular degeneration (AMD). 33 …”
Section: Increased Vascular Permeabilitymentioning
confidence: 99%
“…C5a-stimulated human umbilical vein endothelial cells show up-regulation of genes for E-selectin, intracellular adhesion molecule-1, vascular cell adhesion molecule-1, and IL-6. 32 Anaphylatoxins also influence the expression of adhesion molecules on leukocytes. It has been postulated that C5a is involved in eosinophil adhesion to bronchial epithelial cells during allergic inflammation in the airways.…”
Section: Leukocyte Extravasationmentioning
confidence: 99%
See 1 more Smart Citation
“…It also stimulates mast cell degranulation , mast cell chemotaxis in specific mast cell subtypes (Hartmann et al, 1997, McCloskey et al, 1999, oxidative burst in granulocytes and the production of reactive oxygen species (ROS) in neutrophils , secretion of lysosomal enzymes from macrophages (McCarthy and Henson, 1979) and polymorphonuclear (PMN) cells as well as the secretion of proinflammatory mediators from monocytes, eosinophils (Takafuji et al, 1994) and mast cells (Hartmann et al, 1997). C5a is also responsible for upregulation of vascular adhesion molecules such as E-selectin, inter-cellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) after systemic activation of complement (Albrecht et al, 2004, Jagels et al, 2000. Our preliminary findings suggest that C5a can promote human mast cell adhesion to extracellular matrix protein, as well as human mast cell migration in vitro, indicating a critical role of C5a/C5aR in inflammation.…”
Section: Biological Rolementioning
confidence: 67%